2018
DOI: 10.3389/fmicb.2018.02040
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Year Persistence of Verotoxigenic Escherichia coli (VTEC) in a Closed Canadian Beef Herd: A Cohort Study

Abstract: In this study, fecal samples were collected from a closed beef herd in Alberta, Canada from 2012 to 2015. To limit serotype bias, which was observed in enrichment broth cultures, Verotoxigenic Escherichia coli (VTEC) were isolated directly from samples using a hydrophobic grid-membrane filter verotoxin immunoblot assay. Overall VTEC isolation rates were similar for three different cohorts of yearling heifers on both an annual (68.5 to 71.8%) and seasonal basis (67.3 to 76.0%). Across all three cohorts, O139:H1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 145 publications
(217 reference statements)
2
14
0
Order By: Relevance
“…Shahrani et al, [29] and Akter et al, [30] concluded that VT1 is the most prevalent than VT2. Prevalence of 51% among calves was obtained by Wang et al, [31] which was closely contact to our finding. Higher prevalence 83% among diarrheic calves was obtained by Pervez et al, [32].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Shahrani et al, [29] and Akter et al, [30] concluded that VT1 is the most prevalent than VT2. Prevalence of 51% among calves was obtained by Wang et al, [31] which was closely contact to our finding. Higher prevalence 83% among diarrheic calves was obtained by Pervez et al, [32].…”
Section: Discussionsupporting
confidence: 92%
“…Prevalence of STEC infection in human was 15% by Salmanzadeh-Ahrabi et al, [35], 2.3% by Rajendran et al, [36], 1.7% by van Duynhoven et al, [37], 7% was reported in patients with diarrhoea in Morogoro, Tanzania in 2006 by Raji et al, [38] and 56% by Matussek et al, [39]. The overall prevalence of virulence-associated gene VT1 only, VT2 only, VT1 and VT2 and eaeA were 10.7%, 20.8%, 68.5%, 3.9%, respectively as reported by Wang et al, [31]. Pervez et al, [32] reported that 10% of the isolates of calves were positive for VT1 gene while eaeA not detected.…”
Section: Discussionmentioning
confidence: 79%
“…Herd characteristics and sample collection for VTEC have been described previously [39]. Briefly, 38 yearling heifers from three consecutive cohorts (10 to 16 individuals per cohort-year) from the Canadian Food Inspection Agency (CFIA)-National Centre for Animal Disease (NCAD) (Lethbridge, Alberta, Canada) Angus-Hereford cross research herd were sampled for VTEC on a monthly basis between April 2012 and March 2015.…”
Section: Bacterial Isolatesmentioning
confidence: 99%
“…Sporadic serotypes were defined as those isolated on two sampling dates or fewer overall. The population structure of VTEC within this herd has been characterized previously [39]. This was used to assess for possible lineage effects that may confound the GWAS by ensuring that persistent and sporadic serotypes were not stratified by lineage; thus, leading to the identification of lineage-specific rather than phenotype-specific loci.…”
Section: Genome-wide Association Study (Gwas) Of Persistent Versus Spmentioning
confidence: 99%
See 1 more Smart Citation